Particularism About Arguments - Alhambra, José (Informal Logic, 2024)
The aim of this paper is to develop the notions of particularism and generalism in argumentation theory. Generalism is the claim that to argue we need general rules that specify which data support which conclusions, while particularism denies it. The problem is that it is not always clear what these rules consist of, and in what sense argumentation depend on them. To clarify this, I will first introduce the discussion in moral philosophy and show how it has been adapted to argumentation theory. Then I will distinguish some ways of understanding rules and contend that their alleged necessity might be supported in at least three ways. This will allow me to identify some variants of generalism and, on this basis, to outline what I consider to be the most promising reading of particularism.